Neuromodulation With Thoracic Dorsal Root Ganglion Stimulation Reduces Ventricular Arrhythmogenicity - Kuwabara, Yuki; Salavatian, Siamak; Howard-Quijano, Kimberly; Yamaguchi, Tomoki; Lundquist, Eevanna; Mahajan, Aman (Frontiers in Physiology, 2021)
Introduction: Sympathetic hyperactivity is strongly associated with ventricular arrhythmias and sudden cardiac death. Neuromodulation provides therapeutic options for ventricular arrhythmias by modulating cardiospinal reflexes and reducing sympathetic output at the level of the spinal cord. Dorsal root ganglion stimulation (DRGS) is a recent neuromodulatory approach; however, its role in reducing ventricular arrhythmias has not been evaluated. The aim of this study was to determine if DRGS can reduce cardiac sympathoexcitation and the indices for ventricular arrhythmogenicity induced by programmed ventricular extrastimulation. We evaluated the efficacy of thoracic DRGS at both low (20 Hz) and high (1 kHz) stimulation frequencies. Methods: Cardiac sympathoexcitation was induced in Yorkshire pigs (n = 8) with ventricular extrastimulation (S1/S2 pacing), before and after DRGS. A DRG-stimulating catheter was placed at the left T2 spinal level, and animals were randomized to receive low-frequency (20 Hz and 0.4 ms) or high-frequency (1 kHz and 0.03 ms) DRGS for 30 min. High-fidelity cardiac electrophysiological recordings were performed with an epicardial electrode array measuring the indices of ventricular arrhythmogenicity—activation recovery intervals (ARIs), electrical restitution curve (Smax), and Tpeak–Tend interval (Tp-Te interval). Results: Dorsal root ganglion stimulation, at both 20 Hz and 1 kHz, decreased S1/S2 pacing-induced ARI shortening (20 Hz DRGS −21±7 ms, Control −50±9 ms, P = 0.007; 1 kHz DRGS −13 ± 2 ms, Control −46 ± 8 ms, P = 0.001). DRGS also reduced arrhythmogenicity as measured by a decrease in Smax (20 Hz DRGS 0.5 ± 0.07, Control 0.7 ± 0.04, P = 0.006; 1 kHz DRGS 0.5 ± 0.04, Control 0.7 ± 0.03, P = 0.007), and a decrease in Tp-Te interval/QTc (20 Hz DRGS 2.7 ± 0.13, Control 3.3 ± 0.12, P = 0.001; 1 kHz DRGS 2.8 ± 0.08, Control; 3.1 ± 0.03, P = 0.007). Conclusions: In a porcine model, we show that thoracic DRGS decreased cardiac sympathoexcitation and indices associated with ventricular arrhythmogenicity during programmed ventricular extrastimulation. In addition, we demonstrate that both low-frequency and high-frequency DRGS can be effective neuromodulatory approaches for reducing cardiac excitability during sympathetic hyperactivity.